A Prominent Figure For The Living Human Treasures List In meddah-Ship: Yusuf Sira From Kadirli - Simsek, Esma (Geleneksel Yayincilik Ltd Stl, 2015)
Story telling tradition which is not alive as it was before, is still keeping alive in Cukurova region. Those who lived in this tradition is Yusuf Sira who lives. in Bekereci village of Kadirli. He known as Ashik Yusuf and a master storyteller who continues the tradition of meddah-ship by various aspects. Yusuf Sira who narrates beautiful tales with his ability to imitation, imagination and wit, tells the Ouzel Ahmet and Esma Han tales in addition to Koroglu tales that he learned from the ashiks who came their house at his childhood and he tells them properly. Also he knows some of turkus (Bey Kizi. and Huseyin, collo, Karacaoglan and Ham) that involves a short tale. Moreover, Sira performs Gode, Deve, Kocakari, Sinsin and Serce spectacles which are performed at the villages, serves Abdal Aga duty during the weddings and leads Anatolian folk dance called halay. Yusuf Sira has learned playing kaval while he was a shepherd, and he also plays sipsi. Sira is a very good anecdote teller as well as being a poet. Yusuf Sira who shows skills of a meddah in many aspects, is a performer who has introduced himself to the science world as having two graduate thesis, two papers, four articles on him He, With the specialties above, is one of the names who must be added to the UNESCO's Living Human Treasures List like Neset Ertas, Seref Tashova, Maksut Koca, Halime Ogut, Mehmet Gursoy etc. hi this article, Yusuf Sira's tale telling in other words meddah-ship Will be evaluated from many as-pects and justifications will be given that why he has to be added to the Living Human Treasures List.
Keywords: Yusuf Sira; Kaairli; storyteller; meddah; living human treasure